Tumbuhan Herbal Sebagai Alternatif Penghambat Bakteri Streptococcus Mutans dalam Terapi Karies Gigi - Moch. Diky Alifuddin; Abdul M Ukratalo; Fiyogi Derandy A Tuhumury (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Dental caries is one of the most common dental health problems worldwide, caused by bacterial activity in the mouth, notably Streptococcus mutans. This bacterium plays a crucial role in tooth demineralization, ultimately leading to tooth decay. The management of dental caries is typically performed through medical procedures, such as dental fillings; however, this method does not prevent the recurrence of caries. One alternative that has gained attention is the use of herbal plants. This article explores using herbal plants as an alternative inhibitor of Streptococcus mutans bacteria in treating dental caries. The writing of this article employs a narrative analysis approach by collecting secondary data from various previous studies. The exploration results show that 33 herbal plants are used as therapies for addressing dental caries, with five plants being the most commonly used: betel leaf, Lantana camara, lime, celery, and ginger. Using herbal plants to inhibit Streptococcus mutans offers promising potential for developing more natural, safe, and affordable treatment methods.